Improvement of the sampling method for Scots pine (Pinus sylvestris L.) wood used to evaluate specific activity of 137 Cs - Krasnov, V. P.; Zhukovskyi, O. V.; Orlov , O. O. (Forestry and Forest Melioration, 2020)
Introduction The main tree species are the main edificators of forests and play a significant economic role. Therefore, after the Chernobyl accident, numerous studies have been conducted on radioactive contamination of parts and organs of tree species, radial distribution of 137Cs in the stem, as well as the distribution of the total activity of this radioactive element in forest ecosystems. In their papers, researchers have noted low levels of radioactive contamination of wood, but the materials obtained by different scientists for the same tree species and at the same levels of radioactive contamination of the soil had quite different values of radionuclide content in the stem. The aim of the research was to establish the regularities in radial distribution of 137Cs in the wood of Scots pine (Pinus sylvestris L.) to substantiate the method of wood sampling for scientific research and radiation control of wood products. Materials and Methods The publication is based on the materials of the research conducted on the temporary test area (TTA) in Povchansky Forestry (compartment 49, subcompartment 11) of the State Enterprise “Luhyny Forestry” in 1997. At the TTA (with an area of 1 hectare) the stand had the following silvicultural and mensuration characteristics: composition – 100 per cent of Scots pine, age – 80 years, relative density of stocking – 0.7, site index – II, forest site conditions – fresh infertile pine site type (A2). As a result of an overall enumeration of the trees, the parameters of the average model trees for the three central stages of thickness were established. Consequently, the trees, which are close in mensuration indicators to the average model, were selected at the TTA and cut down. The stems of the trees were divided into 2-meter segments. At that, 4-centimetre-thick circles of wood were cut on their tops and placed into packages with a label (tree number, height of wood collection). In laboratory conditions, annual wood rings formed over 5-year intervals (from 1993 to 1923) were singled out on each circle of wood. The selected wood was cut from the periphery of the ring to the middle, crushed, dried and analyzed on a multi-channel gamma spectrum analyzer of impulses SEG-005-AKP with the BDEG-20-P1 and BDEG-20-P2 scintillation detectors. Results and Conclusions The results indicated a decrease in the specific activity of 137Cs in the wood of the Scots pine stem from the periphery to its center. In the root part of the stem, the decrease reaches 4.7 times (from 4,730 ? 348 to 1,000 ? 117 Bq·kg-1). This indicator was also lower in wood in the same years of formation, but at different heights. Thus, the value of this indicator in the wood formed in 1997–1993 near the root was 4,730 ? 348 Bq·kg-1, while at a height of 22 m it was 2,870 ? 148 Bq·kg-1 (1.6 times less). In radioecological studies aimed at determining the average specific activity of 137Cs in stem wood, it is necessary to take wood samples every 1–2 meters along the length of the stem and then to calculate the average value based on all the data obtained for this indicator at all stem heights. Each sample must equally present wood of all years of its formation at a given height. Equability of representation in the wood sample of all years of its formation can be ensured by sampling to the stem center with a Pressler increment borer and, after sawing the tree, with a chainsaw by preparing sawdust with a continuous section of the stem (annual rings). 4 Tables, 21 Refs. Key words: wood, Scots pine, specific activity, 137Cs, radioactive contamination, radionuclides.